Bleeding management in patients with new oral anticoagulants - Vargas, Maria; Marra, Annachiara; Perrone, Antonietta; Servillo, Giuseppe (Minerva anestesiologica, 2016)
New oral anticoagulants (NOACs) have been developed in recent years and are increasingly used in clinical practice. Dabigatran is a direct thrombin (factor II) inhibitor while rivaroxaban, apixaban and edoxaban are direct inhibitors of factor Xa. The European Medicines Agency (EMA) currently approves these NOACs for different clinical uses. NOACs do not require routine monitoring of coagulation although an assessment of anticoagulation activity in these patients may be required in different conditions. NOACs show a similar or lower incidence of bleeding compared with conventional therapies in phase III trials. In case of bleeding, non-specific reversal strategies are available while specific reversal agents are the subject of ongoing trials. The role of this review is to summarize the current knowledge on NOCAs focusing on bleeding management in the perioperative period.